DETERMINANTS OF FINANCIAL PERFORMANCE OF STATE- OWNED ENTERPRISES IN INDONESIA AND THAILAND - Gilang Kharisma Putra; Sherli Junianingrum; Rahul Bhandari; Mohamad Saufi Che Rusuli (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
The purpose of this study is to analyze and present empirical data on the effects of institutional ownership, a board of independent commissioners, a board of directors, an audit committee, and managerial ownership on the financial performance of state-owned companies in Indonesia and Thailand that are listed on the Indonesia Stock Exchange (IDX) and the Stock Exchange of Thailand (SET) from 2014 to 2021. Purposive sampling was used to gather 120 samples for the study, including 32 samples in Thailand and 120 samples in Indonesia. The data analysis technique used in this study is multiple regression analysis. The results of this study show that institutional ownership has a negative effect on the financial performance of state-owned businesses in Thailand and Indonesia, the audit committee has a positive effect on that performance, and the board of directors has a negative effect on that performance